CHARACTER EDUCATION VALUES IN THE HISTORICAL GLOCALIZATION OF FOLKTALE SEWAWAR WATERFALL - Iqbal Syahrul Akbar Al Aziz; Ani Rakhmawati; Nugraheni Eko Wardani (Vol. 2 No. 1 (2024): Proceeding of International Conference on Cultures & Language 2024, 2024)
This research explores the concept of historical glocalization in the context of the Sewawar Waterfall folktale and its impact on character education values in local communities. Folktale is certainly an important part of a society's cultural heritage and often reflects the values cherished by that society. This research analyzes character education values such as religious values, honesty, tolerance, love of peace, social care and environmental care reflected in the folktale of Sewawar Waterfall, as well as how these values experience a historical glocalization process in the context of local culture and history. This type of research uses descriptive qualitative with an ethnographic approach. Data was collected through interviews with local community leaders, cultural figures, Kuncen, and local historical documentation studies. The research results show that the character education values in these folktales have undergone significant adaptation according to the historical and cultural context of local communities, creating a unique form of historical glocalization phenomenon. The implication of this research is a deeper understanding of how character education values have played a role in shaping the cultural and moral identity of local communities, as well as their relevance in the current global character education context.